An enhancement of slicing test algorithm for integration testing of embedded system - Madey, Ahmed Sheikh Abdullahi (2014)
The complexity of testing the software of Component Based Software Development (CBD) for Embedded Real Time (ERT) software development highlight the challenges of designing, analyzing and testing ERT software. From this standpoint, the complexities of CBD for ERT in software testing require suitable software algorithms. Against these claims, a number of software testing algorithms have been formulated such as slicing algorithm, incremental algorithm, firewall algorithm, genetic algorithm as well as simulated annealing algorithm. Generally, not all of these algorithms support CBD and ERT software testing of the system. By applying slicing algorithm into ERT software testing, the complexity of ERT software development can be decreased and at the same time promote high degree of reuse through software testing based on component behavior. Currently, testing algorithm based on slicing does not directly support ERT software. In this research, the integration testing algorithm for CBD and ERT system has been proposed to represent a promising way to test ERT software in terms of algorithm refinement. The slicing algorithm called slicing architectures using service edges (SASE) has been enhanced to support a component oriented programming (COP) framework for CBD and ERT integrated system. The results shows that COP framework can be applied into SASE algorithm definitions and it has been mapped with the SASE algorithm based on the similarities and differences definitions. Thus, the quality of the enhanced SASE algorithm is better in terms of algorithm criteria based on Normative Information Model-based Systems Analysis and Design (NIMSAD) evaluation in support of ERT and CBD